2018
DOI: 10.1093/ajh/hpy102
|View full text |Cite
|
Sign up to set email alerts
|

Increased Resting Heart Rate on Electrocardiogram Relative to In-office Pulse Rate Indicates Cardiac Overload: The J-HOP Study

Abstract: A decreased delta HR was positively associated with the BNP level and LVMI. Without the requirement of a special technique, this evaluation might indicate potential cardiac overload and provide a clinical sign related to heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The main limitation of our study is that both baseline and in-trial RHRs were measured using automated office BP measurement (AOBPM). Previous differences were found between the pulse rate assessed by the physician and the heart rate obtained via electrocardiography [ 22 ]. The method of RHR estimation in the current study was not verified against other methods.…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of our study is that both baseline and in-trial RHRs were measured using automated office BP measurement (AOBPM). Previous differences were found between the pulse rate assessed by the physician and the heart rate obtained via electrocardiography [ 22 ]. The method of RHR estimation in the current study was not verified against other methods.…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate is an important indicator that is easily accessible and does not require advanced technical equipment. High heart rate is associated with increased CV events, both in the general human population and in people with CV risk factors [3] . In the Framingham Study, heart rate was found to be associated with mortality in men and women who are patients with hypertension [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Heart rate is an important indicator that is easily accessible and does not require advanced technical equipment. High heart rate is associated with increased CV events, both in the general human population and in people with CV risk factors [3]. In the Framingham Study, heart rate was found to be associated with mortality in men and women who are patients with HT [4].…”
Section: Introductionmentioning
confidence: 99%